Reflectance spectroscopy (250–2500 nm) of an aggregate sample from asteroid (101955) Bennu - E.A. Cloutis; D.M. Applin; A.A. Simon; B.E. Clark; X.-D. Zou; V.E. Hamilton; R.E. Milliken; T. Hiroi; M.E. Zolensky; K.M. Peters; L.P. Keller; D.N. DellaGiustina; et al. (Icarus, 2026)

Nutrition Services in Oncology: A Cross-Sectional Survey of Patient Experiences, Needs, and Gaps in Care - Bailey M. Foster; Melissa F. Miller; Colleen K. Spees; Cynthia A. Thomson; Elaine B. Trujillo; Erica E. Fortune; Lauren Fay; Peter A. Adintori; Renee Stubbins; Jill M. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2026)

Evaluating Hg speciation in an offshore gas export pipeline and the utility of pXRF for screening Hg contamination - Lhiam Paton; Bernt Johannessen; Peter Kappen; Pauline Treble; Jessica Hamilton; Tom Cresswell (Journal of Hazardous Materials, 2026)

Characterising subsea gas pipeline contaminants to inform decommissioning practices, an ecosystem perspective - Tom Cresswell; Henri Wong; Matthew Johansen; Peter Kappen; Jessica Hamilton; Francesca Gissi; Sue Brown; Lhiam Paton; Simon Apte (Journal of Hazardous Materials, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Microbial dispersal from a hyperactive sandsheet in the Icelandic Highland - Nathan Hadland; Christopher W. Hamilton; Peter Schroedl; Federica Calabrese; Jeffery Marlow; Solange Duhamel (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Frequent disturbance to a foundation species disrupts consumer‐mediated nutrient cycling in giant kelp forests - Joseph R. Peters; Daniel C. Reed; June Shrestha; Scott L. Hamilton; Deron E. Burkepile (Ecology, 2025)
Structure‐forming foundation species facilitate consumers by providing habitat and refugia. In return, consumers can benefit foundation species by reducing top‐down pressures and increasing the supply of nutrients. Consumer‐mediated nutrient dynamics (CND) fuel the growth of autotrophic foundation species and generate more habitat for consumers, forming reciprocal feedbacks. Such feedbacks are threatened when foundation species are lost to disturbances, yet testing these interactions requires long‐term studies, which are rare. Here, we experimentally evaluated how disturbance to giant kelp, a marine foundation species, affects (1) CND of the forest animal community and (2) nutrient feedbacks that help sustain forest primary production during extended periods of low nitrate. Our experiment involved removing giant kelp annually during the winter for 10 years at four sites to mimic frequent wave disturbance. We paired temporal changes in the forest community in kelp removal and control plots with estimates of taxon‐specific ammonium excretion rates (reef fishes and macroinvertebrates) and nitrogen (N) demand (giant kelp and understory macroalgae) to determine the effects of disturbance on CND as measured by ammonium excretion, N demand by kelp forest macroalgae, and the percentage of nitrogen demand met by ammonium excretion. We found that disturbance to giant kelp decreased ammonium excretion by 66% over the study, mostly due to declines in fishes. Apart from a few fish species that dominated CND, most reef‐associated consumers were unaffected by disturbance. Disturbance to giant kelp reduced its N demand by 56% but increased that of the understory by 147% due to its increased abundance in the absence of a kelp canopy. Overall, disturbance had little effect on the fraction of N demand of macroalgae met by consumer excretion due to the offsetting responses of giant kelp, understory macroalgae, and consumers to disturbance. Across both disturbance regimes, on average, consumers supported 11%–12% of the N required by all kelp forest macroalgae and 48% of N demand by the understory macroalgae (which are confined to the benthos where most reef‐associated consumers reside). Our findings suggest that CND constitutes a considerable contribution of N required in kelp forests, yet nutrient inputs decrease following reductions in essential habitat perpetuated by frequent disturbances.

Biomarker-based high-throughput sperm phenotyping: Andrology in the age of precision medicine and agriculture - Filip Tirpak; Lauren E. Hamilton; Robert D. Schnabel; Peter Sutovsky (Animal Reproduction Science, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

The absence of genotoxicity of Aloe vera beverages: A review of the literature - Sang-Tae Kim; Peter Pressman; Roger Clemens; Allison Moore; Ryan Hamilton; A. Wallace Hayes (Food and Chemical Toxicology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cyanobacteria species dominance and diversity in three Australian drinking water reservoirs - Benny Zuse Rousso; Edoardo Bertone; Rodney A. Stewart; Sara P. Hughes; Peter Hobson; David P. Hamilton (Hydrobiologia, 2022)
The objective of this study was to identify correlations between environmental variables and cyanobacterial diversity, succession and dominance in three Australian water supply reservoirs. We assessed up to 15 years of in-lake water quality monitoring data from Lake Wivenhoe and Lake Tingalpa (Queensland), and Lake Myponga (South Australia). Lakes Wivenhoe and Tingalpa, subject to a subtropical climate, had higher cyanobacterial richness than Lake Myponga in temperate South Australia. Richness in the subtropical lakes was positively correlated ( P < 0.05) with total cyanobacteria biomass, and cyanobacteria biovolume > 0.03 mm 3 /l (Alert level 1; World Health Organization) was often composed of multiple cyanobacteria species. Peaks in total cyanobacteria biomass and diversity occurred in all three lakes from late spring to early autumn. Unicellular picocyanobacterial dominance was negatively correlated ( P < 0.05) with total nitrogen while dominance of colonial and filamentous species with larger cells (e.g. Microcystis spp., Raphidiopsis spp., Dolichospermum circinale ) was positively correlated ( P < 0.05) with total phosphorus. Among the species with larger cells, diazotrophic D. circinale often dominated when total nitrogen was at low concentrations. Our results support decision making for selecting cyanoHAB control strategies based on single- or multi-species dominance and reinforce that new monitoring technologies could support species-level assessments.

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function - Lauren M. Ashwood; Eivind A. B. Undheim; Bruno Madio; Brett R. Hamilton; Marymegan Daly; David A. Hurwood; Glenn F. King; Peter J. Prentis (Molecular Ecology, 2022)
The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structures in Telmatactis stephensoni . Specifically, using a combination of proteomic and transcriptomic approaches, we examined whether there is a direct correlation between the functional similarity of regions and the similarity of their associated toxin expression profiles. We report that the regionalization of toxin production is consistent with the partitioning of the ecological roles of venom across envenomating structures, and that three major functional regions are present in T . stephensoni : tentacles, epidermis and gastrodermis. Additionally, we find that most structures that serve similar functions not only have comparable putative toxin profiles but also similar nematocyst types. There was no overlap in the putative toxins identified using proteomics and transcriptomics, but the expression patterns of specific milked venom peptides were conserved across RNA‐sequencing and mass spectrometry imaging data sets. Furthermore, based on our data, it appears that acontia of T . stephensoni may be transcriptionally inactive and only mature nematocysts are present in the distal portions of the threads. Overall, we find that the venom profile of different anatomical regions in sea anemones varies according to its ecological functions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global co‐occurrence of methanogenic archaea and methanotrophic bacteria in Microcystis aggregates - Chuang Li; K. David Hambright; Hannah G. Bowen; Majoi A. Trammell; Hans‐Peter Grossart; Michele A. Burford; David P. Hamilton; Helong Jiang; Delphine Latour; Elisabeth I. Meyer; Judit Padisák; Richard M. Zamor; et al. (Environmental Microbiology, 2021)
Summary Global warming and eutrophication contribute to the worldwide increase in cyanobacterial blooms, and the level of cyanobacterial biomass is strongly associated with rises in methane emissions from surface lake waters. Hence, methane‐metabolizing microorganisms may be important for modulating carbon flow in cyanobacterial blooms. Here, we surveyed methanogenic and methanotrophic communities associated with floating Microcystis aggregates in 10 lakes spanning four continents, through sequencing of 16S rRNA and functional marker genes. Methanogenic archaea (mainly Methanoregula and Methanosaeta ) were detectable in 5 of the 10 lakes and constituted the majority (~50%–90%) of the archaeal community in these lakes. Three of the 10 lakes contained relatively more abundant methanotrophs than the other seven lakes, with the methanotrophic genera Methyloparacoccus , Crenothrix , and an uncultured species related to Methylobacter dominating and nearly exclusively found in each of those three lakes. These three are among the five lakes in which methanogens were observed. Operational taxonomic unit (OTU) richness and abundance of methanotrophs were strongly positively correlated with those of methanogens, suggesting that their activities may be coupled. These Microcystis ‐aggregate‐associated methanotrophs may be responsible for a hitherto overlooked sink for methane in surface freshwaters, and their co‐occurrence with methanogens sheds light on the methane cycle in cyanobacterial aggregates.

Angioplasty Induced Changes in Dialysis Vascular Access Compliance - Yihao Zheng; Brian J. Thelen; Nirmala Rajaram; Venkataramu N. Krishnamurthy; James Hamilton; Miguel Angel Funes-Lora; Timothy Morgan; Lenar Yessayan; Brandie Bishop; Nickolas Osborne; Peter Henke; Albert J. Shih; et al. (Annals of Biomedical Engineering, 2021)

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Advances in Continuous Active Pharmaceutical Ingredient (API) Manufacturing: Real-time Monitoring Using Multivariate Tools - Melanie Dumarey; Martin Hermanto; Christian Airiau; Peter Shapland; Hannah Robinson; Peter Hamilton; Malcolm Berry (Journal of Pharmaceutical Innovation, 2019)

A process of convergent amplification and tissue‐specific expression dominates the evolution of toxin and toxin‐like genes in sea anemones - Joachim M. Surm; Hayden L. Smith; Bruno Madio; Eivind A.B. Undheim; Glenn F. King; Brett R. Hamilton; Chloé A. van der Burg; Ana Pavasovic; Peter J. Prentis (Molecular Ecology, 2019)
Members of phylum Cnidaria are an ancient group of venomous animals and rely on a number of specialized tissues to produce toxins in order to fulfil a range of ecological roles including prey capture, defence against predators, digestion and aggressive encounters. However, limited comprehensive analyses of the evolution and expression of toxin genes currently exist for cnidarian species. In this study, we use genomic and transcriptomic sequencing data to examine gene copy number variation and selective pressure on toxin gene families in phylum Cnidaria. Additionally, we use quantitative RNA‐seq and mass spectrometry imaging to understand expression patterns and tissue localization of toxin production in sea anemones. Using genomic data, we demonstrate that the first large‐scale expansion and diversification of known toxin genes occurs in phylum Cnidaria, a process we also observe in other venomous lineages, which we refer to as convergent amplification. Our analyses of selective pressure on sea anemone toxin gene families reveal that purifying selection is the dominant mode of evolution for these genes and that phylogenetic inertia is an important determinant of toxin gene complement in this group. The gene expression and tissue localization data revealed that specific genes and proteins from toxin gene families show strong patterns of tissue and developmental‐phase specificity in sea anemones. Overall, convergent amplification and phylogenetic inertia have strongly influenced the distribution and evolution of the toxin complement observed in sea anemones, while the production of venoms with different compositions across tissues is related to the functional and ecological roles undertaken by each tissue type.

Potential for offsetting diamond mine carbon emissions through mineral carbonation of processed kimberlite: an assessment of De Beers mine sites in South Africa and Canada - Evelyn M. Mervine; Sasha Wilson; Ian M. Power; Gregory M. Dipple; Connor C. Turvey; Jessica L. Hamilton; Sterling Vanderzee; Mati Raudsepp; Colette Southam; Juerg M. Matter; Peter B. Kelemen; Johann Stiefenhofer; et al. (Mineralogy and Petrology, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Isotopically (δ13C and δ18O) heavy volcanic plumes from Central Andean volcanoes: a field study - C. Ian Schipper; Yves Moussallam; Aaron Curtis; Nial Peters; Talfan Barnie; Philipson Bani; H. J. Jost; Doug Hamilton; Alessandro Aiuppa; Giancarlo Tamburello; Gaetano Giudice (Bulletin of Volcanology, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Changes in river water quality caused by a diversion hydropower dam bordering the Pantanal floodplain - Ibraim Fantin-Cruz; Olavo Pedrollo; Pierre Girard; Peter Zeilhofer; Stephen K. Hamilton (Hydrobiologia, 2016)

Western Juniper Management: Assessing Strategies for Improving Greater Sage-grouse Habitat and Rangeland Productivity - Shahla Farzan; Derek J. N. Young; Allison G. Dedrick; Matthew Hamilton; Erik C. Porse; Peter S. Coates; Gabriel Sampson (Environmental Management, 2015)

Ten ways remote sensing can contribute to conservation - Robert A. Rose; Dirck Byler; J. Ron Eastman; Erica Fleishman; Gary Geller; Scott Goetz; Liane Guild; Healy Hamilton; Matt Hansen; Rachel Headley; Jennifer Hewson; Ned Horning; et al. (Conservation Biology, 2015)
In an effort to increase conservation effectiveness through the use of Earth observation technologies, a group of remote sensing scientists affiliated with government and academic institutions and conservation organizations identified 10 questions in conservation for which the potential to be answered would be greatly increased by use of remotely sensed data and analyses of those data. Our goals were to increase conservation practitioners’ use of remote sensing to support their work, increase collaboration between the conservation science and remote sensing communities, identify and develop new and innovative uses of remote sensing for advancing conservation science, provide guidance to space agencies on how future satellite missions can support conservation science, and generate support from the public and private sector in the use of remote sensing data to address the 10 conservation questions. We identified a broad initial list of questions on the basis of an email chain‐referral survey. We then used a workshop‐based iterative and collaborative approach to whittle the list down to these final questions (which represent 10 major themes in conservation): How can global Earth observation data be used to model species distributions and abundances? How can remote sensing improve the understanding of animal movements? How can remotely sensed ecosystem variables be used to understand, monitor, and predict ecosystem response and resilience to multiple stressors? How can remote sensing be used to monitor the effects of climate on ecosystems? How can near real‐time ecosystem monitoring catalyze threat reduction, governance and regulation compliance, and resource management decisions? How can remote sensing inform configuration of protected area networks at spatial extents relevant to populations of target species and ecosystem services? How can remote sensing‐derived products be used to value and monitor changes in ecosystem services? How can remote sensing be used to monitor and evaluate the effectiveness of conservation efforts? How does the expansion and intensification of agriculture and aquaculture alter ecosystems and the services they provide? How can remote sensing be used to determine the degree to which ecosystems are being disturbed or degraded and the effects of these changes on species and ecosystem functions?

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

TMEM43 mutations associated with arrhythmogenic right ventricular cardiomyopathy in non-Newfoundland populations - Berivan Baskin; Jon R. Skinner; Shubhayan Sanatani; Deborah Terespolsky; Andrew D. Krahn; Peter N. Ray; Stephen W. Scherer; Robert M. Hamilton (Human Genetics, 2013)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Fish mediate high food web connectivity in the lower reaches of a tropical floodplain river - Timothy D. Jardine; Bradley J. Pusey; Stephen K. Hamilton; Neil E. Pettit; Peter M. Davies; Michael M. Douglas; Vivian Sinnamon; Ian A. Halliday; Stuart E. Bunn (Oecologia, 2012)

Biological nitrogen fixation in acidic high‐temperature geothermal springs in Yellowstone National Park, Wyoming - Trinity L. Hamilton; Rachel K. Lange; Eric S. Boyd; John W. Peters (Environmental Microbiology, 2011)
Summary The near ubiquitous distribution of nifH genes in sediments sampled from 14 high‐temperature (48.0–89.0°C) and acidic (pH 1.90–5.02) geothermal springs in Yellowstone National Park suggested a role for the biological reduction of dinitrogen (N 2 ) to ammonia (NH 3 ) (e.g. nitrogen fixation or diazotrophy) in these environments. nifH genes from these environments formed three unique phylotypes that were distantly related to acidiphilic, mesophilic diazotrophs. Acetylene reduction assays and 15 N 2 tracer studies in microcosms containing sediments sampled from acidic and high‐temperature environments where nifH genes were detected confirmed the potential for biological N 2 reduction in these environments. Rates of acetylene reduction by sediment‐associated populations were positively correlated with the concentration of NH 4 + , suggesting a potential relationship between NH 4 + consumption and N 2 fixation activity. Amendment of microcosms with NH 4 + resulted in increased lag times in acetylene reduction assays. Manipulation of incubation temperature and pH in acetylene reduction assays indicated that diazotrophic populations are specifically adapted to local conditions. Incubation of sediments in the presence of a N 2 headspace yielded a highly enriched culture containing a single nifH phylotype. This phylotype was detected in all 14 geothermal spring sediments examined and its abundance ranged from ∼780 to ∼6800 copies (g dry weight sediment) −1 , suggesting that this organism may contribute N to the ecosystems. Collectively, these results for the first time demonstrate thermoacidiphilic N 2 fixation in the natural environment and extend the upper temperature for biological N 2 fixation in terrestrial systems.

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

The plankton community of Lake Matano: factors regulating plankton composition and relative abundance in an ancient, tropical lake of Indonesia - Elisabeth Sabo; Denis Roy; Paul B. Hamilton; Peter E. Hehanussa; Roger McNeely; G. Douglas Haffner (Hydrobiologia, 2008)

Processes regulating the community composition and relative abundance of taxa in the diatom communities of the Malili Lakes, Sulawesi Island, Indonesia - Andrew J. Bramburger; Paul B. Hamilton; Peter E. Hehanussa; G. Douglas Haffner (Hydrobiologia, 2008)

Cooling lakes while the world warms: Effects of forest regrowth and increased dissolved organic matter on the thermal regime of a temperate, urban lake - Tanentzap Andrew J.; Yan Norman D.; Bill Keller; Robert Girard; Jocelyne Heneberry; John M. Gunn; David P. Hamilton; Peter A. Taylor (Limnology and Oceanography, 2008)
Depending on the magnitudes and directions of changes in air temperatures, winds, and underwater light attenuation, lakes may either warm or cool. Here we report a 28‐yr decrease in the whole‐lake average temperature of Clearwater Lake, Canada, despite regional signatures of climate warming. Using a one‐dimensional lake mixing model, we demonstrate that this pattern was attributable to a 35% reduction in surface wind speeds, itself explained by forest regrowth following local SO 2 emission reductions and tree planting, and a 10‐fold increase in dissolved organic carbon concentrations causing a substantial increase in vertical light attenuation following deacidification of the lake. Long‐term trends in lake temperatures do not necessarily follow those of air temperatures. The Clearwater Lake data demonstrate that any factors that influence local wind speeds and underwater light attenuation should be considered as modifiers of the effects of climate warming on lake thermal regimes.

OCCURRENCE, COMPOSITION, AND POTENTIAL FUNCTIONS OF NORTH ATLANTIC RIGHT WHALE ( EUBALAENA GLACIALIS ) SURFACE ACTIVE GROUPS - Susan E. Parks; Moira W. Brown; Lisa A. Conger; Philip K. Hamilton; Amy R. Knowlton; Scott D. Kraus; Christopher K. Slay; Peter L. Tyack (Marine Mammal Science, 2007)
Marine mammal social interactions are poorly understood primarily because of the difficulty of observing these behaviors in the wild. Observations of copulations in North Atlantic right whale surface active groups (SAGs) have led to the hypothesis that the function of these groups is for conception. The occurrence and composition of SAGs sighted from 1992 to 2001 were investigated on the basis of age, sex, and reproductive status of individuals. A total of 918 SAG events were documented. SAGs were observed in all habitat areas and in all months in which right whales were sighted. Group compositions revealed both potentially conceptive groups and nonconceptive groups. Of right whales whose age was known, 93% were first sighted in SAGs as juveniles, and more than half of all observed groups contained at least one juvenile whale. The group composition and timing of occurrence of SAGs do not support the hypothesis that all groups serve a purely conceptive function. Their functional role is likely much broader. Other potential functions include play, mating practice, or maintenance of social bonds.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Shorebirds, snails, and the amphipod (Corophium volutator) in the upper Bay of Fundy: top–down vs. bottom–up factors, and the influence of compensatory interactions on mudflat ecology - Diana J. Hamilton; Antony W. Diamond; Peter G. Wells (Hydrobiologia, 2006)

Venom yields from Australian and some other species of snakes - Peter J. Mirtschin; Nathan Dunstan; Ben Hough; Ewan Hamilton; Sharna Klein; Jonathan Lucas; David Millar; Frank Madaras; Timothy Nias (Ecotoxicology, 2006)

THE GUNSHOT SOUND PRODUCED BY MALE NORTH ATLANTIC RIGHT WHALES ( EUBALAENA GLACIALIS ) AND ITS POTENTIAL FUNCTION IN REPRODUCTIVE ADVERTISEMENT - Susan E. Parks; Philip K. Hamilton; Scott D. Kraus; Peter L. Tyack (Marine Mammal Science, 2005)
A bstract North Atlantic right whales ( Eubalaena glacialis ) make a short, distinctive broadband sound that is produced internally called a Gunshot sound. This sound has been recorded in the Bay of Fundy, Canada from both single whales ( n = 9) and social surface active groups ( n =49). Those single whales producing Gunshot sounds whose sex could be determined ( n = 9) were all mature males. Gunshot sounds were produced as part of a stereotyped behavioral sequence by these individuals, including frequent head‐lifts and flipper slapping at the surface. In surface active groups, Gunshot sounds were commonly recorded when males were present in the group. The rate of production of Gunshot sounds was weakly correlated with the total number of males present in the group. Given the behavioral context of Gunshot sound production, and production of the sound only by male whales, Gunshots may function in a reproductive context as an advertisement signal to attract females, an agonistic signal directed toward other males, or a combination of the two functions.

Localisation and functional studies on the 5′ -nucleotidase of the cattle tick Boophilus microplus - Nancy Liyou; Susan Hamilton; Robert McKenna; Chris Elvin; Peter Willadsen (Experimental and Applied Acarology, 2000)